FTIR STUDY OF TWO DIFFERENT LIGNITE LITHOTYPES FROM NEOCENE ACHLADA LIGNITE DEPOSITS IN NW GREECE - Oikonomopoulos, I.; Perraki, Th.; Tougiannidis, N. (Bulletin of the Geological Society of Greece, 2010)
The FTIR spectra for both Neogene xylite and matrix lignite samples from Achlada NW Greece show significant differences, which are mainly evident in aliphatic stretching region (3000-2800 cm-1) where the intensities of the vibrations are reduced in matrix lignite lithotype compared to xylite one. The intense bands in the region 3402-3416 cm-1 are attributed to -OH stretching of H2O and phenol groups. The bands at ~3697 cm-1 and ~3623 cm-1 as well as at ~538 cm-1 and 470 cm-1, which are more evident in the FTIR spectra of matrix lignite, are attributed to higher content of clay minerals in the samples of this lithotype. The stretching vibration appears at ~1032 cm-1 is intense in all matrix lignite samples and it is broadening in the xylite ones. The FTIR spectra of all samples confirm the progressive elimination of aliphatic vibrations from xylite lithotype to matrix lignite one and the appearance of clay minerals in the latter. As a whole the FTIR spectra of both xylite and matrix lignite confirm the significant differences between these two lignite lithotypes.